2018
DOI: 10.19044/esj.2018.v14n28p173
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality and Relationship Quality as Antecedents and Predictors of Loyalty in the Chemical Industry: A Literature Review

Abstract: Several kinds of research in the past examined relationship quality as antecedents in B2B industries. The literature review extends a prior study by linking perceived quality with relationship quality as antecedents and predictors of customer loyalty. This study is a review of customer loyalty antecedents with the chemical industry as a content object. Perceived quality has two dimensions of tangible product and service. Referring to past research, there is no single universal relationship quality framework. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The conceptual model that combines the CRM model and the three variables is the novel contribution of this study to the development of relationship-based marketing models. Samudro et al (2018a) investigated the relationship between perceived quality and trust/satisfaction, trust and commitment, commitment and loyalty, and satisfaction and loyalty using the CRM model. This research is very important to conduct since the loan industry is experiencing quite intense competition.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual model that combines the CRM model and the three variables is the novel contribution of this study to the development of relationship-based marketing models. Samudro et al (2018a) investigated the relationship between perceived quality and trust/satisfaction, trust and commitment, commitment and loyalty, and satisfaction and loyalty using the CRM model. This research is very important to conduct since the loan industry is experiencing quite intense competition.…”
Section: Introductionmentioning
confidence: 99%
“…Some past studies confirm the positive relationship between customer satisfaction and loyalty, wherein loyalty is a consequence of customer satisfaction (Lam et al, 2004;Rauyruen & Miller, 2007;Ulaga et al, 2006). Thus, the positive relationships between customer satisfaction and loyalty have been widely acknowledged in the past by scholars, researchers, and business practitioners (Jani & Han, 2014;Kaur & Soch, 2018;Samudro et al, 2018a;Sharma, 2017;Watson et al, 2015).…”
Section: Customer Satisfaction and Brand Loyaltymentioning
confidence: 87%
“…One barrier that prevents businesses from developing a good relationship with their customers is that the customers may expect more from their purchase and the provider than what they receive (Samudro et al 2018). To overcome this barrier, businesses need to establish trust with their customers, which is often best accomplished through more than one interaction (e.g., the purchase), which in turn will require them to expand their offerings and improve their customer service.…”
Section: Value Co-creation and Customer Value In The B2b Industrymentioning
confidence: 99%
“…To overcome this barrier, businesses need to establish trust with their customers, which is often best accomplished through more than one interaction (e.g., the purchase), which in turn will require them to expand their offerings and improve their customer service. Samudro et al (2018) suggested two different aspects from which to examine the customer's perceived value. The first one was the product or service itself, which is its core and most fundamental value.…”
Section: Value Co-creation and Customer Value In The B2b Industrymentioning
confidence: 99%